2009
DOI: 10.1209/0295-5075/87/60004
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric cost in snowdrift game on scale-free networks

Abstract: We study the effects of asymmetric cost on the cooperative behavior in the snowdrift game on scale-free networks. The asymmetric cost reflects the inequality in mutual cooperation and the diversity of cooperators. We focus on the evolution of cooperation and the inequality in wealth distribution influenced by the degree of asymmetry in cost, related with cooperators' connections. Interestingly, we find that when cooperators with more neighbors have the advantage, cooperative behavior is highly promoted and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
73
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(73 citation statements)
references
References 52 publications
0
73
0
Order By: Relevance
“…Then we choose one of agent x's nearest neighbors at random, and the chosen agent y also acquires its payoff P y by the same rule. We suppose that the probability that agent x adopts agent y's opinion is given by the Fermi function [27][28][29][30]:…”
mentioning
confidence: 99%
“…Then we choose one of agent x's nearest neighbors at random, and the chosen agent y also acquires its payoff P y by the same rule. We suppose that the probability that agent x adopts agent y's opinion is given by the Fermi function [27][28][29][30]:…”
mentioning
confidence: 99%
“…Consequently, (11) can be proven by induction, which completes the proof. The time when the number of cooperators in the population equals that in A, plays a key role in the rest of the proof.…”
Section: Now Letmentioning
confidence: 64%
“…While these assumptions help to simplify the mathematical setup and gain insight into the theoretical aspects of cooperation mechanisms, an interesting research line that has not been explored to its full potential is to study a finite heterogeneous population of game-playing agents under stochastic discrete-time updating dynamics. [7] Interesting simulation results have been conducted for heterogeneous populations in [11], [12] and [13] where the agents are associated with different payoff matrices. Some mathematical statements have been provided in [14] and [15] The work was supported in part by the European Research Council (ERCStG-307207).…”
Section: Introductionmentioning
confidence: 99%
“…Other prominent mechanisms that support the evolution of cooperation include kin selection [12], mobility and dilution [13,14], direct and indirect reciprocity [15,16], network reciprocity [11,[17][18][19], * marcoantonio.amaral@gmail.com group selection [20], and population heterogeneity [21][22][23][24]. In particular, research in the realm of statistical physics has shown that properties of the interaction network can have far reaching consequences for the outcome of evolutionary social dilemmas [25][26][27][28][29][30][31][32][33][34][35][36][37] (for reviews see Refs. [38][39][40][41][42][43][44]), and moreover, that heterogeneity in general, be it introduced in the form of heterogeneous interaction networks, noisy disturbances to payoffs, or other player-specific properties like the teaching activity or the propensity to acquire new links over time, is a strong facilitator of cooperation [22,37,[45][46][47][48][49][50][51]…”
Section: Introductionmentioning
confidence: 99%